P17.14 Barriers and facilitators to couples hiv testing and counselling and views on incentives for couples testing: a qualitative study from zimbabwe. (13th September 2015) - Sibanda, EL; Makamba, M; Hatzold, K; Cowan, FM
Abstract : Introduction: Couples HIV testing (CHTC) has greater health impact and is more cost-effective than individual testing. Despite widespread promotion, uptake remains sub-optimal. We explored i) barriers and facilitators to CHTC, ii) anticipated impact of incentives on CHTC uptake and linkage to post-test services, iii) incentives which might stimulate CHTC. Methods: Focus group discussions (FGDs) were held among rural Zimbabweans. FGDs started with role plays depicting couples with differing circumstances to stimulate discussion and were transcribed verbatim and analysed thematically. Results: Four FGDs were held with 17 men and 17 women. Both sexes said men were opposed to CHTC; barriers were more pertinent to men. The main barrier was fear of HIV diagnosis which respondents firmly believed would result in relationship dissolution. Participants understood discordancy as possible but were unaware/had not internalised benefits of discordant couple interventions. Discussions focused on the difficulty of broaching CHTC within a relationship as it raises uncomfortable issues of distrust. Women reportedly broached CHTC if they suspected infidelity, often threatening suicide or relationship dissolution in the event they tested positive. Interventions that took the decision out of the couple's hands e.g. perceived 'mandatory testing' for prevention of mother-to-child-transmission were viewed as facilitators for CHTC. Participants unanimously agreed that incentives would make discussing CHTC easier as the focus would shift to incentives. Participants said small items such as food and soap would stimulate CHTC. Participants were against monetary incentives as these would likely be abused or lead to conflict. Small, fixed incentives were preferred over larger lottery-based incentives. Participants said couples who received incentives to test would be more likely to link to post-test services with expectation of receiving additional rewards. Conclusion: This study suggests that small non-financial incentives may increase uptake of CHTC and subsequent linkage to care. We propose to test this intervention in a cluster randomised trial. Disclosure of interest statement: The study was funded by the Integrated Support Programme and no conflicts of interest are declared.